Adaptive Expression of Forgotten Engrams - Autore, Livia (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2023)
Long-term memories are stored as stable configurations of neuronal ensembles, termed engrams. While investigation of engram cell properties and functionality in memory recall has been extensive, less is known about how engram cells are affected by forgetting. In this work I studied, described and manipulated two different forms of forgetting: retroactive interference and extinction learning. Retroactive interference occurs when new incoming information impairs the consolidation of a previously encoded memory. On the other hand extinction learning is defined as the behavioral attenuation that occurs when a CS is presented repeatedly without the US it had been previously associated with. By using activity-dependent cell labelling, optogenetic stimulation and inhibition and neuronal population recordings, I assessed whether these two types of forgetting consists of a suppression of the original memory rather than an erasure or updating of it. I showed that although retroactive interference and extinction both result in decreased engram cell reactivation during recall trials, and that optogenetic stimulation of the labelled engram cells is sufficient to induce memory retrieval following interference but not following extinction learning. Forgotten engrams may also be reinstated via the presentation of similar or related environmental information. Furthermore, I demonstrate that engram activity is necessary for interference to occur. Taken together, these findings indicate that forgetting modulates engram expression in a manner that is both reversible and updatable. Both these forms of forgetting may constitute a form of adaptive forgetting, where in everyday life new perceptual and environmental inputs modulate the natural forgetting process.
APPROVED
Keywords: Forgetting; Engrams; Behavior; Optogenetics; Memory; Mice